Effect of Active Knowledge Sharing Strategy on Learning Outcomes of Students with Hearing Impairment in Learning Fractions - Nurkholifah, Dira Rosalia; Akhlan, Riksma Nurahmi Rinalti; Hernawati, Tati (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The low understanding of basic fraction concepts among students with hearing impairment has led to difficulties in writing fractional numbers and performing addition and subtraction of fractions. This study aims to examine the effect of the active knowledge-sharing strategy on the learning outcomes in fractions of students with hearing impairment at SLBN Cicendo, Bandung City, specifically in writing simple fractions and performing addition and subtraction fractions with like denominators. This research used an experimental method using a one-group pretest-posttest design. The subjects were six students from Class VIII-A1 with hearing impairment. Data were collected through pretests and post-tests post-tests and analyzed using the Wilcoxon Signed Rank Test. The results showed that the average post-test score was higher than the average pretest score. The most significant improvement was observed in the indicator for calculating the addition and subtraction results of common fractions with like denominators. In contrast, the lowest improvement was found in the indicator for writing simple fractions using concrete and semi-concrete media.